Key principles for the provision of high quality telecommunication services 4G mobile users at speeds up to 300 km/h - Sunduchkov, Аrtem; Sunduchkov, Konstantin (Видавництво Львівської політехніки, 2012)
In this paper on the example of the network, which delivers signals 4G services mobile users moving at speeds up to 300 km/h, considered issues of quality of these services [1]. Schematically shows the architecture of building such network. Defines the key principles of quality signal transmission service 4G mobile terminal moving at speeds up to 300 km/h.
Keywords: mobile communications; digital signal processing; OFDM- technology